The strategy of coercive isolation U.S. security policy - Timonthy W. Crawford (2014)
The isolation of adversaries is an important form of coercive diplomacy. Because countries that are isolated are more vulnerable to military force and more exposed to the costs of fighting, the diplomatic process of being isolated puts coercive pressure on them. This paper focuses on the theory and practice of such diplomacy—what I call “coercive isolation.” We first present conceptual model of the strategy, which highlights the logic of how it works. Then we examine three different ways in which it can be used—immediate deterrence, blackmail, and compellence—and discuss the costs and difficulty of succeeding in these contexts. Historical examples of each of the three scenarios are examined to illuminate important dimensions of the model. From this discussion we also draw several conclusions about the conditions that favour the success of coercive isolation strategies. Finally, we examine the role and utility of coercive isolation in three problem areas of U.S. security policy—humanitarian intervention, counter-proliferation, and regime change.